TIMBULAN, KOMPOSISI, DAN POTENSI DAUR ULANG SAMPAH DARI BERBAGAI SUMBER DI KOTA PADANG - Yenni Ruslinda (Purifikasi, 2010)
Data of generation, composition, and recycling potential of solid waste are needed for designing, evaluating, and developing municipal solid waste (MSW) management system in a particular region. From this research, it was found that the average residential solid waste generation rates in Padang was 2.66 L or 0.38 kg/person×day, and that of commercial sources was 3.82 L or 0.52 kg/person×day. The solid waste generation rate of institutional sources was 1.37 L or 0.11 kg/person×day, and that of industrial sources was 6.57 L or 5.06 kg/person×day. The municipal services contributed solid waste of 1.80 L or 0.19 kg/person×day. Solid waste composition from several sources in Padang consisted of biodegradable organic waste of 25-83%, and plastic, paper, metal and other solid waste materials of 17-75%. The main source of biodegradable organic waste was municipal services (82.85%), whereas other waste materials were generated from industrial waste (75.37%). Waste components that have a potential to be recycled are food wastes, yard wastes, wood, paper, plastics, glass, tin cans, copper, zinc, and metal. The MSW recycling potential was 59-89%, and those of biodegradable organic waste and other waste materials were of 22-78% and 11-55% respectively. The highest recycling potential of biodegradable organic waste was from municipal services and institutional sources, whereas that of the other waste materials was from commercial, domestic, and industrial sources.